2007
DOI: 10.1021/ic700468m
|View full text |Cite
|
Sign up to set email alerts
|

[Mo(TmMe)(O)2Cl]:  An Alternative Functional Model of Sulfite Oxidase

Abstract: The hydrotris(methimazolyl)borate anion (TmMe) has been used to synthesize an alternative functional model ([Mo(TmMe)(O)2Cl]) of the metalloenzyme sulfite oxidase. It has been shown that the complex undergoes oxygen atom transfer chemistry and that it performs the primary function of the enzyme, sulfite oxidation. A method using ion chromatography has been developed to definitively prove that sulfite is oxidized to sulfate. Employment of a soft tripodal ligand has allowed us to tune the redox potentials of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Hydrotris(3‐methyl‐1‐imidazolyl‐2‐thione)borate (Tm Me , 22 ) complexes have also attracted attention as enzyme models especially as they exhibit a sulfur‐rich coordination sphere like Mo‐MPT enzyme active sites. Complexes of this type were simultaneously reported by the groups of Reglinski and Carrano . Both groups reported the synthesis, crystal structure and OAT reactivity of [Tm Me MoO 2 Cl].…”
Section: Oat and Cept Reactionsmentioning
confidence: 88%
See 1 more Smart Citation
“…Hydrotris(3‐methyl‐1‐imidazolyl‐2‐thione)borate (Tm Me , 22 ) complexes have also attracted attention as enzyme models especially as they exhibit a sulfur‐rich coordination sphere like Mo‐MPT enzyme active sites. Complexes of this type were simultaneously reported by the groups of Reglinski and Carrano . Both groups reported the synthesis, crystal structure and OAT reactivity of [Tm Me MoO 2 Cl].…”
Section: Oat and Cept Reactionsmentioning
confidence: 88%
“…The dioxido complex is also capable of catalyzing the oxidation of PPh 3 to OPPh 3 using Me 2 SO as oxidant, emulating the reactions catalyzed by DMSOR . Significantly, Reglinski and co‐workers reported that [Tm Me MoO 2 Cl] mimics SO activity by oxidizing sulfite to sulfate, a rarely reported reaction in Mo enzyme model chemistry.…”
Section: Oat and Cept Reactionsmentioning
confidence: 99%
“…Studies from several laboratories have demonstrated that a variety of discrete oxo-molybdenum(VI) complexes can carry out the atom transfer chemistry when reacted with oxygen atom abstractors producing oxidized species such as tertiary phosphines oxides, sulfoxides, N-oxides, tertiary arsine-oxide, or sulfate [6][7][8][9][10][11][12][13][14][15][16][17]. Using tertiary phosphines (PR 3 ), we have demonstrated that OAT reactions from [Mo VI O 2 ] 2+ cores proceed in steps involving the formation of a phosphoryl coordinated Mo(IV) center which losses the phosphoryl ligand, and the vacant site is occupied by a solvent molecule [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the first structurally characterized zinc hydroxide complex supported by a tridentate sulfur ligand, (Tm Ph )ZnOH, was prepared as a structural model for the zinc-containing enzyme 5-aminolevulinate dehydratase (ALAD) [124]. A couple of Tm Me complexes of molybdenum stoichiometrically convert sulfite to sulfate and thereby serve as functional models for sulfite oxidase [125,126]. The unusual trigonal pyramidal cation [(Tm Ph )Pb] + ( Fig.…”
Section: Tris(mercaptoimidazolyl)boratesmentioning
confidence: 99%